Aplicação do método FDTD para avaliação da resposta de linhas de transmissão e aterramentos elétricos frente a descargas atmosféricas - Victor Alves Silva e Melo (2017)
This work presents the basic concepts related to the Finite Difference Time Domain (FDTD) method and the development of a computational modeling tool based on this method to obtain the lightning response of transmission lines and grounding. The application of the method requires only the knowledge of the geometry of the system under investigation and of the electrical constants of the medium, such as resistivity and permittivity, without simplifications being adopted for representing system elements. The computational implementation was developed using MatLab software and it was applied for calculating voltages and currents in different electrical systems presented in papers of great relevance in the area and simulated by the Hybrid Electromagnetic Model . The results of ground potential rise and overvoltage in transmission line insulator strings show good agreement, suggesting the applicability of the computational tool for lightning related analyses. The comparison with results obtained by measuements in reduced-scale systems, such as parallel conductors used to crosstalk effect analysis and horizontal conductors used to potential wave reflection analysis, indicated small differences, reaching 5% in the most critical cases. The simulations of transmission lines and grounding yielded results very close to those obtained with the Hybrid Electromagnetic Model, with the largest differences being less than 15% and 5% in the peak and tail values of the overvoltages, respectively